HISTORY AND DEVELOPMENT OF PESANTREN IN INDONESIA - Indah Wahyu Ningsih; Hasan Basri; Andewi Suhartini (Universitas Labuhanbatu, 2023)
The research explains the traces of the history and development of Islamic boarding schools in Indonesia using the research method of the library research approach (library research), literature studies are defined as a series of activities related to the method of collecting library data, reading, recording and processing research materials. The results of this study suggest that pesantren is one of the main educational pillars in the development of Islam in the archipelago, historically, pesantren is an inseparable part of the life of the Indonesian people, because in reality the growth of pesantren is in line with the development of Islam in Indonesia. The role of pesantren is not only as an educational institution that educates, guides and trains students, pesantren is also one of the historical forces that is the background of Islamic movements that have emerged in Indonesia. Pesantren is also a sokoguru of Islamic education in Indonesia which has a role not only as an educational institution to educate students but as an institution that plays an active role in fighting for independence and building a unitary state of the republic of IndonesiaKeywords : History, Development, BoardingÂ AbstrakPenelitian menjelaskan jejak sejarah dan perkembangan pesantren di Indoneisa dengan menggunakan metode penelitian pendekatan kepustakaan (library research), studi kepustakaan diartikan sebaga serangkaian kegiatan yang berkenaan dengan metode pengumpulan data pustaka, membaca, mencatat dan megolah bahan penelitian. Hasil penelitian ini menunujukan pesantren merupakan salah satu pilar pendidikan utama dalam perkembangan agama Islam di Nusantara, Secara historis, pesantren adalah bagian yang tidak bisa dipisahkan dari kehidupan masyarakat Indonesia, karena secara realita pertumbuhan pesantren sejalan dengan perkembangan Islam di Indonesia. Peran pesantren tidak hanya sebagai lembaga pendidikan yang mendidik, membimbing dan mengkader para santri, pesantren juga menjadi salah satu kekuatan sejarah yang menjadi latar belakang gerakan-gerakan Islam yang muncul di Indonesia. Pesantren juga sebagai sokoguru pendidikan Islam di Indonesia yang memiliki peran tidak hanya sebagai lembaga pendidikan untuk mendidik para santri melainkan juga sebagai lembaga yang berperan aktif berjuang meraih kemerdekaan dan membangun Negara Kesatuan Republik IndonesiaKata Kunci : Sejarah, Perkembangan, Pesantren